Antara Hukum Islam dan Adat; Sistem Baru Pembagian Harta Warisan - Siregar, Fatahuddin Aziz (Jurnal el-Qanuniy: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2019)
The South Tapanuli community adopts a patrilineal kinship system so that women do not get inheritance, even if there is acquisition of property, women receive it not in their capacity as heirs but in the form of holong ni ate as confirmed in the Supreme Court Jurisprudence number 506K / Sip / 1968 dated January 22, 1969 However, on the other hand the Tapsel community underwent a process of Islamization that was quite deep, so that the customary law of South Tapanuli was also influenced by positive law including Jurisprudence which gave heir to girls later issued by the Supreme Court number 528K / Sip / 1972 dated 17 January 1973. This rule makes the practice of distributing the assets of Tapsel's community inheritance also shifts no longer according to the full provisions of adat law.This paper focuses on answering the factors that cause the shift in Batak customary inheritance in Tapsel, how the form of Batak adat inheritance shifts in Tapsel, and how the role of Islamic law in the shifting Batak customary inheritance in Tapsel. To answer this, use descriptive-analytical field research using data collection techniques in the form of observations and interviews with traditional leaders, religious leaders, judges and the community who carry out the distribution of inheritance.From this search, the authors found that the practice of inheritance in Tapsel society has shifted from adat inheritance caused by two factors, namely, First, the factor of Islamic law because Tapsel people have understood Islam well and run it in various fields of life including in the distribution of inheritance. Given that there are dozens of Islamic education institutions in Tapsel according to the author has given a pretty good understanding of Islamic law. So in general it can be said, that this change is a consequence of the Islamization process experienced by the Tapsel people. Second, is the factor of higher power or positive law because until now the community still believes that only the Religious Courts as a place to solve the problem of inheritance to obtain legal certainty.The shift to adat inheritance occurs in several patterns. The first pattern is a total change from customary form to division according to faraid, this pattern occurs in areas that are fairly Islamic, namely the Mandailing Natal region, although of course there are some people who divide in a way that is not consistent in carrying out Islamic law. The second pattern is to carry out adat law, namely in communities that are relatively strict with adat, namely in the Padang Lawas and Sipirok regions, in this area many cases seem to have carried out faraid formally but the substance still reflects the spirit of adat law. The third pattern, namely the way of division which is a combination of Islamic law and customary law, which is a fairly moderate community in the Angkola region.Islamic law has contributed by shifting the implementation of customary law to Islamic law. People who according to customary law do not receive inheritance become heirs who receive a certain portion. At first the mother did not count as an heir, then given a part 1/3 or 1/6. Istdri initially did not get any portion of the inheritance then received 1/4 or 1/8. Girls initially only have the status of olong ate, then receive a relatively large portion, which is 1/2 or 2/3.